2017
DOI: 10.1098/rsos.170798
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic deposition of carbon nanotube on reticulated vitreous carbon for hexavalent chromium removal in a biocathode microbial fuel cell

Abstract: For Cr(VI)-removal microbial fuel cell (MFC), a more efficient biocathode in MFCs is required to improve the Cr(VI) removal and electricity generation. RVC-CNT electrode was prepared through the electrophoretic deposition of carbon nanotube (CNT) on reticulated vitreous carbon (RVC). The power density of MFC with an RVC-CNT electrode increased to 132.1 ± 2.8 mW m−2, and 80.9% removal of Cr(VI) was achieved within 48 h; compared to only 44.5% removal of Cr(VI) in unmodified RVC. Cyclic voltammetry, energy-dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The removal rate of Cu(II) in the sediment attained 57%, which was 1.7 times higher than that of the non-biocathode MFC. Fei et al (2017) constructed a three-dimensional biocathode by loading carbon nanotubes (RVC-CNT) on reticulated glassy carbon. They found that RVC-CNT significantly promoted the electrical conductivity and electron-transfer rate of the biocathode, providing more reaction sites for the reduction of Cr(VI).…”
Section: Key Factors Affecting the Removal Of Heavy Metals Using Bioc...mentioning
confidence: 99%
“…The removal rate of Cu(II) in the sediment attained 57%, which was 1.7 times higher than that of the non-biocathode MFC. Fei et al (2017) constructed a three-dimensional biocathode by loading carbon nanotubes (RVC-CNT) on reticulated glassy carbon. They found that RVC-CNT significantly promoted the electrical conductivity and electron-transfer rate of the biocathode, providing more reaction sites for the reduction of Cr(VI).…”
Section: Key Factors Affecting the Removal Of Heavy Metals Using Bioc...mentioning
confidence: 99%
“…For example, monolithic three-dimensional (3D) electrodes with porous structures have increased the effective electroactive surface area (EASA) for microbial loading. [13][14][15] Despite some recent success in improving the biocurrent density extracted from cells using this approach, clogging of the electrode remains a concern for long-term applications. [16,17] Other methods for developing 3D electrodes have relied on the design of electrodes with shape-adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Al films were arranged on Al alloy and prepared along with stainless steel substrates using a combination of HCl/H 2 O 2 etching and electrophoretic deposition (EPD) [31].…”
Section: Introductionmentioning
confidence: 99%